Maxillary sinus tuberculosis: a case report - Keles, E.; Karlidag, T.; Demirpolat, N.; Ozden, M. (Galenos Yayincilik, 2012)
Paranasal sinus tuberculosis is considerably scarce because paranasal sinus mucosa has natural resistant to the invasion of pathogen. In this study, a 62-aged male patient who had Caldwell-Luc operation with pre-diagnosis of left maxillary sinus mycetoma and applied with the complaint of incessant defluxion in the gingivobuccal incision line following the operation was presented. Maxillary sinus tuberculosis was diagnosed in the patient our case was discussed with literature in order to emphasis the significance of tuberculose in differential diagnosis of unilateral paranasal lesions.
Keywords: Paranasal sinus; maxillary sinus; tuberculose